L'étiquetage des aliments irradiés et la liberté d'expression - Corriveau, Manon (Les Cahiers de droit, 1988)
Faced with technological advances in the field of food preserving methods, Canadian consumers are concerned and call for legislative action to require food processing industries to clearly indicate "irradiated food" on product labels. The author questions the constitutionality of such action. After having attempted to define the meaning of the concept "freedom of expression " (Canadian Charter of Rights and Freedoms, Subsection 2.b) to see if it includes commercial speech as well as the right to remain silent, the author sets out to determine whether such measures constitute a "reasonable limit that can be demonstrably justified in a free and democratic society."